H2 PRODUCTION THROUGH WATER GAS SHIFT REACTION AT MEDIUM TEMPERATURE USING CU/MCM-41 NANOCATALISTS - Khairunida' Shalihah, Rawiyah
The East Natuna Gas Field has 222 TCF (trillion cubic feet) of natural gas reserves, with 46 TCF of processable gas. The high CO2 content, which reaches 71%-vol, makes it difficult to utilize this natural gas as fuel. However, the presence of CO2 and CH4 in this natural gas is an advantage for producing synthesis gas through the dry reforming of methane (DRM) reaction. The synthesis gas from DRM has an H2/CO ratio of 1–3 with a high CO content in the synthesis gas. This becomes a limitation in the application of synthesis gas for fuel cell and feed for ammonia production. The CO content in the synthesis gas from DRM can be reduced through water gas shift (WGS) reaction. Operating WGS at medium temperature (MTS) is a strategy to overcome the thermodynamic limitation of this reaction. WGS feed in the form of DRM synthesis gas and operating conditions at MTS are not compatible with existing commercial catalysts. Therefore, it is necessary to develop catalysts that produce good activity in MTS with the feed of DRM synthesis gas. MCM-41 is a mesoporous SiO2-based material with a pore size of 20–100 Å. This material is suitable to be used as a support for MTS catalyst because the presence of these mesoporous pores makes the diffusion of reactants easier and allows the accessibility of reactants to approach the active site of the catalyst. This study aims to examine the use of Cu/MCM-41 catalysts and variations in Cu loading on the physico-chemical properties and catalyst activity for the WGS reaction under MTS conditions. This research was conducted through 3 stages, namely catalyst synthesis, catalyst characterization, and catalyst activity test. The synthesis of Cu/MCM-41 catalyst was carried out through impregnation method with Cu loading variation of 10, 15, 20, and 25%-wt. The four catalysts were given initials namely Kat-A, Kat-B, Kat-C, and Kat-D, respectively. Characterization of the synthesized catalysts was carried out using XRD, XRF, N2- physisorption, H2-TPR, and SEM. The catalyst activity test was conducted using a fixed bed reactor with steady-state operating conditions at atmospheric pressure, temperature 325oC, and WHSV of 12,000 mL/gram-hour. The feed gas used for the activity test consists of two types, namely DRM gas mix which has a composition of iv 25%-vol CH4, 10%-vol CO2, 15%-vol CO, and 50%-vol H2 and 25%-vol CO. The molar ratio of steam to CO was 3. The results showed that the synthesis of Cu/MCM-41 catalyst through impregnation method was successful without changing the mesoporous structure of MCM-41. The increase in Cu loading resulted in increased CO conversion, with the highest average CO conversion produced by Kat-D at 26.28%. The use of 25%-vol CO feed showed that the Cu/MCM-41 catalyst was able to suppress methane formation. However, there was a decrease in the number of moles of H2 in all Cu/MCM-41 catalysts, indicating a greater reverse water gas shift (RWGS) reaction than WGS. Thus, Cu/MCM-41 catalyst is less suitable to be used for WGS reaction with DRM synthesis gas feed at MTS condition.